Macroeconomic Determinants of Investment Decisions for Medium and Large Enterprises in Poland’s Manufacturing Sector - Adam Andrzej Zając; Michał Wielechowski; Krzysztof Smoleń; Dariusz Karaś (Gospodarka Narodowa. The Polish Journal of Economics)
This article examines how fluctuations in macroeconomic indicators influence companies’ propensity to invest, gauged by the investment intensity index – defined as the ratio of investment expenditures to total revenue. The analysis focuses on the five most revenue-generating sectors within Poland’s manufacturing industry, as defined in the Polish Classification of Activities (PKD). Using unpublished Statistics Poland (GUS) quarterly panel data from 2008 to 2022, sourced from the F-01 and F-02 reports, the research targets medium and large companies. Cointegration analysis and the Vector Error Correction Model (VECM) are employed to identify macroeconomic indicators that consistently impact the propensity to invest in specific sectors, while also assessing the presence of investment seasonality. The findings reveal a strong long-term correlation between corporate investments and macroeconomic indicators, capturing both enduring equilibria and transient fluctuations. Significantly, the research uncovers varied macroeconomic impacts on investment decisions, with GDP and SP emerging as pivotal in the chemical sector (PKD-20), and temporal and inter-sectoral dynamics notably influencing the computer and electronics sector (PKD-26). These insights highlight the complexity of macroeconomic effects on investment strategies within Poland’s industrial landscape.